The impact of bipolar spectrum disorders on professional functioning: A systematic review - Dominiak, Monika; Jażdżyk, Piotr; Antosik-Wójcińska, Anna Z.; Konopko, Magdalena; Bieńkowski, Przemysław; Świȩcicki, Łukasz; Sienkiewicz-Jarosz, Halina (Frontiers in Psychiatry, 2022)
The impact of bipolar spectrum (BS) disorders on professional functioning has not been systematically reviewed yet. Since even subsyndromal symptoms may disturb functioning, determination of prognostic value of spectrum of bipolarity for employment seems extremely relevant. The aim of this study was to assess the impact of BS disorders on professional functioning. A systematic review of literature (including cohort and cross-sectional studies) investigating a link between BS disorders and employment was performed in accordance with PRISMA guidelines. BS was defined based on a concept of two-dimensional BS (Angst, 2007). Occupational outcomes and factors affecting employment were evaluated as well. Seventy-three studies were included. All disorders comprising BS had a negative impact on occupational status, work performance, work costs and salary, with the greatest unfavorable effect reported by bipolar disorder (BD), followed by borderline personality disorder (BPD), major depression (MDD) and dysthymia. Employment rates ranged from 40-75% (BD), 33-67% (BPD), 61-88% (MDD), 86% (dysthymia). The factors affecting employment most included: cognitive impairments, number/severity of symptoms including subsyndromal symptoms (mainly depressive), older age, education, comorbidity (substance abuse, personality disorders, anxiety, depression, ADHD). BS symptoms exert a negative impact on professional functioning. Further evaluation of affecting factors is crucial for preventing occupational disability.